Expeditions to Knowledge: Routes and Questions (2012)
In the new Expeditions participants can explore each year a different area of knowledge. We call them routes and there are four: Economics and Business, Society and Cultures, Nature Sciences and Engineering. They allow children and young people to freely enter the world and their knowledge, without yet committing to any branch of knowledge.